Supply Chain Optimization - Geunes, Joseph.; Geunes, Joseph.; Pardalos, Panos M.; Pardalos, Panos M. (Applied Optimization,, 2005)
Supply Chain Optimization captures the latest results in a segment of current research activity in supply chain management. This research area focuses on applying optimization techniques to supply chain management problems. The research papers that make up the volume provide a snapshot of state-of-the-art optimization methods within the field. This book presents rigorous modelling approaches for supply chain operations problems with a goal of improving supply chain performance (or the performance of some segment thereof). It contains high-quality works from leading researchers in the field whose expertise fits within this scope. The book provides a diverse blend of research topics and novel modelling and solution approaches for difficult classes of supply chain operations, planning, and design problems. Audience This book is intended for • researchers in supply chain management, applied operations research, and optimization; • industry practitioners in supply chain management with interests in operations management and operations research; • graduate students in supply chain management and optimization-related disciplines.